The Development of Digital Teaching Materials for Basic Excellent Service Based on Google Site for Culinary Vocational Students - Novia Pujiastuti; Sri Handajani; Lucia Tri Pangesthi; Niken Purwidiani (International Journal of Research in Education, 2024)
The purpose of this study is to find out: 1) the results of the development of basic digital teaching materials for excellent service based on Google site platform; 2) the feasibility of materials and media on the basic digital teaching materials of excellent service based on the google site; 3) Student / User Response of Basic Digital Teaching Materials Excellent Service Based on the Google site. This research used research and development (R&D), especially the 4D model according to Thiagarajan. The steps in this model include defining, designing, developing, and disseminating. The data collection technique was carried out using questionnaires with research subjects, consisting of 6 validators (material & media) and 33 culinary students of SMKN8 Surabaya. Data analysis techniques using quantitative descriptive techniques Research shows: 1) digital teaching materials in can be accessed using https://bit.ly/DasarPelayananPrima links; 2) the feasibility of the material and media was declared very feasible with average scores of 92% and 87% respectively: 3) Student response was excellent with an average of 84%. Based on these results, it can be concluded that basic digital teaching materials for excellent service based on Google sites for culinary vocational students are very feasible to apply in culinary basics learning.